Formação de professores: desafios e possibilidades da integração das TIC às práticas de pesquisa - Peruchini, Melise (2017)
This research’s is in the Network Educational Technologies for Innovation and Democratization of Education Area of Concentration, in the Management of Network Education Technologies research line, and its main theme is the integration of the Information and Communication Technologies (ICT) in research practices, aiming to analyses how this integration may be able to help with teacher’s education, transposing teaching and learning challenges, by action-research methodology. Through workshops divided into five topics about different technological tools with a pedagogical use, we looked up to stimulate and analyses the possible contributions of the proposed work. At first, the workshops were offered to the students of “Programa Especial de Graduação - Formação de Professores para Educação Profissional”, from UFSM, at the “Práticas de Investigação no Ensino como Princípio Educativo” curricular discipline. Then, they're open to teachers from city's public schools, as well to graduate students of UFSM, organized by Santa Maria’s Education Department. The development period was two semesters, the first one dedicated to PEG and the second one to the public schools and graduate students. This action-research’s data was collected through activities in the Moodle platform, observations registered in a class diary, and questionnaires. The analysis and discussion of the results point to challenges and possibilities of the integration of ICT in research practices and shows the relevance of teacher’s education, in workshops that presents the new technologies as much as the research practices as a formative principle to professionals of education. As the final product of this work, a courseware in e-book format was elaborated, containing all the workshops processes, to be full disclosure, to ensure information will be widespread and so, allow other professionals of the area to make use of this work.